Coupling imaging mass cytometry with Alcian blue histochemical staining for a single-slide approach - Patrice Hemon; Danivanh Ben-Guigui; Margaux Geier; Margaux Geier; Marine Castillon; Marine Castillon; Corentin Paranthoen; Corentin Paranthoen; Jacques-Olivier Pers; Marion Le Rochais; Arnaud Uguen; Arnaud Uguen (Frontiers in Immunology, 2024)
Imaging mass cytometry (IMC) is a metal mass spectrometry-based method allowing highly multiplex immunophenotyping of cells within tissue samples. However, some limitations of IMC are its 1-µm resolution and its time and costs of analysis limiting respectively the detailed histopathological analysis of IMC-produced images and its application to small selected tissue regions of interest (ROI) of one to few square millimeters. Coupling on a single-tissue section, IMC and histopathological analyses could permit a better selection of the ROI for IMC analysis as well as co-analysis of immunophenotyping and histopathological data until the single-cell level. The development of this method is the aim of the present study in which we point to the feasibility of applying the IMC process to tissue sections previously Alcian blue-stained and digitalized before IMC tissue destructive analyses. This method could help to improve the process of IMC in terms of ROI selection, time of analysis, and the confrontation between histopathological and immunophenotypic data of cells.